Enhancement of the performance of GaP solar cells by embedded In(N)P quantum dots. (July 2015) - Kuang, Yanjin; Sun, Ke; Sukrittanon, Supanee; Takabayashi, Ko; Kamiya, Itaru; Lewis, Nathan S.; Tu, Charles W.
Abstract: Improving the utilization of solar spectra of wide bandgap semiconductors that can potentially provide enough free energy is one of the promising strategies for realizing efficient and spontaneous integrated conversion of solar energy to chemical fuels. We demonstrate herein that nitrogen doped InP quantum dots (QDs) embedded in wide bandgap GaP could improve the solar energy conversion performance. Photoelectrochemical experiments in contact with a nonaqueous, reversible redox couple indicated that the QD-embedded devices exhibited improved performance relative to devices without QDs, with short-circuit current densities increasing from 0.16 mA cm −2 for GaP-only devices to 0.23 and 0.29 mA cm −2 for InP and InNP QD-embedded devices, respectively. Additionally, the open-circuit voltages increased from 0.95 V for GaP-only devices to 1.11 and 1.14 V for InP and InNP QD-embedded devices, respectively, and the external quantum yield of the devices was also enhanced by the embedded QDs. The improvement is attributed to the absorption of sub-bandgap photons by the In(N)P QDs. Graphical abstract: Highlights: InP and InNP quantum dots (QDs) were grown on GaP (100) substrates. InNP QDs have much stronger photoluminescence than InP QDs. Both InP and InNP QDs were embedded in GaP solar cell structures. InNP QDs improve both the short circuit current and open circuit voltage.